2014
DOI: 10.1111/ecog.00845
|View full text |Cite
|
Sign up to set email alerts
|

What do we gain from simplicity versus complexity in species distribution models?

Abstract: 1267 complexity in the occurrence-environment relationships that they fit. Capturing the appropriate amount of complexity for particular study objectives is challenging. By building 'under fit' models, having insufficient flexibility to describe observed occurrence-environment relationships, we risk misunderstanding the factors shaping species distributions. By building 'over fit' models, with excessive flexibility, we risk inadvertently ascribing pattern to noise or building opaque models. As such, determinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
481
1
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 512 publications
(498 citation statements)
references
References 105 publications
3
481
1
13
Order By: Relevance
“…Using one of the most extensive plankton data sets to date, the North Atlantic Continuous Plankton Recorder data, Brun et al (2016) found that a suite of commonly used SDMs are unable to predict and hindcast the distribution of zooplankton and phytoplankton examplespecies on the decadal scale. One way to improve SDMs is either through careful methodological adjustments, such as a targeted selection of the background (Phillips et al, 2009), the reduction of environmental predictors, and model complexity (Merow et al, 2014). Another approach could be to merge existing data archives and to combine genomic data with traditional approaches in order to reduce the sampling bias.…”
Section: Species Distribution Modeling-running Before We Can Walk?mentioning
confidence: 99%
“…Using one of the most extensive plankton data sets to date, the North Atlantic Continuous Plankton Recorder data, Brun et al (2016) found that a suite of commonly used SDMs are unable to predict and hindcast the distribution of zooplankton and phytoplankton examplespecies on the decadal scale. One way to improve SDMs is either through careful methodological adjustments, such as a targeted selection of the background (Phillips et al, 2009), the reduction of environmental predictors, and model complexity (Merow et al, 2014). Another approach could be to merge existing data archives and to combine genomic data with traditional approaches in order to reduce the sampling bias.…”
Section: Species Distribution Modeling-running Before We Can Walk?mentioning
confidence: 99%
“…3 should they exist (additional modeling details are in SI Appendix, section G). Flexible response curves offer the ability to describe more complex responses than we could study with demographic models (because of identifiability) while enforcing smoothness (and avoiding overfitting) and better characterizing the climatic niche (52). To make comparisons, it is important to note that occurrence model predictions are shown in terms of ROR (i.e., given a presence, the relative probability that it was drawn from each cell) (53,54).…”
Section: Methodsmentioning
confidence: 99%
“…In those modelling procedures the spatial distribution of forest species is connected to a set of environmental variables that can be used as predictors modelling procedure (Guisan & Thuiller, 2005;Elith & Leathwick, 2009). A vast number of different SDMs (and ENMs) algorithms have been proposed in the literature, often compared with each other in order to assess their power and suitability according to the different nature of data or species distributions (Zaniewski et al, 2002;Liu et al, 2011;Merow et al, 2014). When a SDM (or an ENM) incorporates future climate predictions, future distribution of species can be forecast becoming a very powerful way to study climate change effects on populations (Forester et al, 2013;Brunetti et al, 2014;IsaacRenton et al, 2014) small parts of species range (Hamann & Aitken, 2013) or provenances (Isaac-Renton et al, 2014).…”
Section: E) Geneticists Had Classified the Black Pine Of Villetta Bamentioning
confidence: 99%